Intestinal Deletion of 3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Promotes Expansion of the Resident Stem Cell Compartment. Issue 4 (17th February 2022) - Doerfler, Alexandria M.; Han, Jun; Jarrett, Kelsey E.; Tang, Li; Jain, Antrix; Saltzman, Alexander; De Giorgi, Marco; Chuecos, Marcel; Hurley, Ayrea E.; Li, Ang; Morand, Pauline; Ayala, Claudia; et al.
Abstract : Background: The intestine occupies the critical interface between cholesterol absorption and excretion. Surprisingly little is known about the role of de novo cholesterol synthesis in this organ, and its relationship to whole body cholesterol homeostasis. Here, we investigate the physiological importance of this pathway through genetic deletion of the rate-limiting enzyme. Methods: Mice lacking 3-hydroxy-3-methylglutaryl-coenzyme A reductase ( Hmgcr ) in intestinal villus and crypt epithelial cells were generated using a Villin -Cre transgene. Plasma lipids, intestinal morphology, mevalonate pathway metabolites, and gene expression were analyzed. Results: Mice with intestine-specific loss of Hmgcr were markedly smaller at birth, but gain weight at a rate similar to wild-type littermates, and are viable and fertile into adulthood. Intestine lengths and weights were greater relative to body weight in both male and female Hmgcr intestinal knockout mice. Male intestinal knockout had decreased plasma cholesterol levels, whereas fasting triglycerides were lower in both sexes. Lipidomics revealed substantial reductions in numerous nonsterol isoprenoids and sterol intermediates within the epithelial layer, but cholesterol levels were preserved. Hmgcr intestinal knockout mice also showed robust activation of SREBP-2 (sterol-regulatory element binding protein-2) target genes in the epithelium, including the LDLR (low-density lipoprotein receptor). At the cellular level, loss of Hmgcr is compensated for quickly after birth through a dramatic expansion of the stem cell compartment, which persists into adulthood. Conclusions: Loss of Hmgcr in the intestine is compatible with life through compensatory increases in intestinal absorptive surface area, LDLR expression, and expansion of the resident stem cell compartment.